Is there a role for professional supervision in supporting the professional and personal wellbeing of the sonographic workforce? A literature review. Issue 4 (November 2022) - Coleman, G.; Hyde, E.
Abstract: Objectives: The sonographer workforce in the UK is under pressure due to chronic staff shortages and increased service demands. The Health and Care Professions Council and the Society of Radiographers both advocate for the use of professional supervision to support wellbeing and development, however the use of professional supervision is not widespread within the sonographer workforce. The aim of this literature review was to explore the evidence around the use of professional supervision and how this could support sonographer wellbeing. Key findings: Professional supervision was found to be of importance for providing emotional support which can lead to increased job satisfaction, lower levels of burnout and subsequently impact on retention of the workforce. Professional supervision supported personal development and therefore increased quality of patient care, allowing professionals to discuss evidence-based care, policies and practice development through reflection. Whilst important for emotional and professional support, this review found that there are conflicting pressures which can impact the effectiveness of supervision including the supervisory relationship itself and time and organisational pressures. Demands on the workforce made a significant impact on the availability of quality clinical supervision. Conclusion: Professional supervision has an important role in supporting the sonography workforce and enable increased wellbeing and emotional support. There are clear benefits to undertaking professional supervision to support the workforce however there are competing demands which may affect the effectiveness of professional supervision. Implications for practice: There is limited international research on the use of professional supervision in the radiographer and sonographer workforce. There are clear benefits for supporting professional wellbeing and development under a structured professional supervision framework however within the United Kingdom there is a significant gap in the literature where further research is required.